THE EFFECT OF CONSUMING AVOCADO (Persea americana) ON MICE (Mus musculus) SPERM QUALITY - Tiara Amelia, Yasinta; Hanizar, Evi; Nur Rikhma Sari, Dwi (BIOVALENTIA: Biological Research Journal, 2021)
The nutrients such as protein and vitamin are proven to improve the sperm quality. One nutrient rich fruit is avocado round green variety, which contains vitamins A, C and E higher than other varieties. This study aimed to determine the effect of consuming avocado on the mice sperm quality. This experimental study was using a Completely Randomized Design with four treatments, each with eight replications. Avocado dosage treatments were control, 75 % w/v, 100% w/v, and 133% w/v , with the number of mice were 32 age four weeks. Avocado was given three times a day, each 0.5 mL for six weeks besides the main food. The observed response was the sperm quality including number, motility and morphology. Sperm was taken from the epididymis after the mice were killed by cervical dislocation method. Sperm was made a suspension using 0.9% NaCl solution and a smear preparation to observe the sperm morphology while staining with basic stain crystal violet. The sperm quality was observed by Neubauer's counting rooms through a multimedia microscope. Data was analyzed using Kurskal Wallis test for the sperm number and Anova test for motility and morphological responses. The result showed that avocado had a significant influence for reproductive health, particularly for increasing spermatozoa quality, including concentration, motility and morphology of sperm. The higher dose of avocado given the higher quantity and quality of sperm resulted.